2008
DOI: 10.1038/nm1726
|View full text |Cite
|
Sign up to set email alerts
|

Engineering attenuated virus vaccines by controlling replication fidelity

Abstract: Long-lasting protection against viral infection is best achieved by vaccination with attenuated viruses. Obtaining stably attenuated vaccine strains has traditionally been an empirical process, which greatly restricts the number of effective vaccines for viral diseases. Here we describe a rational approach for engineering stably attenuated viruses that can serve as safe and effective vaccines. Our approach exploits the observation that restricting viral population diversity by increasing replication fidelity g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
267
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 257 publications
(282 citation statements)
references
References 44 publications
13
267
1
1
Order By: Relevance
“…Eight mutations were detected in 45,000 bases of sequence data from wild-type virion RNA, corresponding to an average of 1.33 mutations per genome. Only two mutations were detected in 45,000 bases of sequence data from G64S virion RNA, corresponding to 0.33 mutation per genome, consistent with the previously reported impact of the G64S mutation on the fidelity of RNA replication (31). The R128A and L420A 3D pol mutations had no significant impact on the fidelity of RNA replication compared to that in wild-type 3D pol (Table 4).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Eight mutations were detected in 45,000 bases of sequence data from wild-type virion RNA, corresponding to an average of 1.33 mutations per genome. Only two mutations were detected in 45,000 bases of sequence data from G64S virion RNA, corresponding to 0.33 mutation per genome, consistent with the previously reported impact of the G64S mutation on the fidelity of RNA replication (31). The R128A and L420A 3D pol mutations had no significant impact on the fidelity of RNA replication compared to that in wild-type 3D pol (Table 4).…”
Section: Resultssupporting
confidence: 88%
“…The fidelity of RNA replication is reported to influence the quasispecies diversity and the pathogenesis of poliovirus infections (27). A G64S mutation in 3D pol renders poliovirus resistant to ribavirin (25), increases the fidelity of RNA replication (26), and attenuates poliovirus replication in mice (26,27,31). Similar fidelity effects are also seen for a K359R mutation that subtly alters a key charged residue that contacts and helps to position the gamma phosphate of the incoming NTP (47).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One crucial mechanism of the high mutation rate for RNA viruses is the low fidelity of RNA-dependent RNA polymerase (RdRp) due to its lack of proofreading ability during RNA replication (Domingo & Holland, 1997;Smith et al, 2013). Studies of poliovirus and other RNA viruses revealed that certain amino acid residues in RdRp are fidelity checkpoints which affect the fidelity of RdRp, and that the fidelity of RdRp can be modulated by change of these checkpoint residues (Gnädig et al, 2012;Rozen-Gagnon et al, 2014;Sadeghipour et al, 2013;Vignuzzi et al, 2008;Zeng et al, 2014). Mutants carrying a high fidelity RdRp showed a decreased population quasispecies diversity and attenuated pathogenicity to hosts (Van Slyke et al, 2015).…”
mentioning
confidence: 99%
“…Mutants carrying a high fidelity RdRp showed a decreased population quasispecies diversity and attenuated pathogenicity to hosts (Van Slyke et al, 2015). Therefore, high fidelity virus mutants could serve as potential safer modified live-attenuated vaccines (MLVs) for RNA viruses (Vignuzzi et al, 2008).…”
mentioning
confidence: 99%